Conscious Clinical Education: The Evidence-Based Education—Clinical Education Model - DeRuiter, Mark; Ginsberg, Sarah M. (Seminars in Speech and Language, 2020)
The fields of speech-language pathology and audiology, collectively referred to as communication sciences and disorders, are driven by evidence-based practice (EBP). As accountability in clinical service delivery continues to increase, there are few who would argue that encouraging clinicians to engage in methods that have withstood the rigors of peer-review is the wrong approach. Graduate students are typically given many opportunities to learn about the evidence for their discipline, and graduate programs are required to provide these opportunities under accreditation standards. While EBP is critical to our discipline's clinical function, we assert that evidence-based education (EBE) is equally as important as EBP to our discipline's function in educating our students. This article discusses EBP and EBE with a focus on elements that may not have been considered in the past, particularly within the complex dynamic of the EBE and clinical education interface. We present current and proposed models, including a new model of EBE in clinical education. We share insights into how the new and proposed models fit within the broader context of clinical decision making and the scholarship of teaching and learning. We conclude by addressing future needs for the education of clinical educators.
Keywords: clinical education; evidence-based practice; communication sciences and disorders; scholarship of teaching and learning; evidence-based education